Penerapan Pendekatan Concrete Representational Abstract Untuk Meningkatkan Hasil Belajar Kognitif Siswa - Khoerun Musthofa (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research motivated by low student learning outcomes. To resolve the issue, given learning using the CRA approach. This research aims to find out student learning outcomes before using the CRA approach in mathematics subjects in Class IV MI Nurul Huda, also to find out student learning outcomes after using the CRA approach in mathematics subjects in Class IV MI Nurul Huda District Paseh, Bandung Regency. The method used is classroom action research methods. This research was carried out in 2 cycles and four actions. Data collection techniques using observation, testing, interview and documentation. Data analysis uses statistics and observation sheets. Subjects consisted of 24 students, 14 women and 10 men. The results of data analysis concluded that (1) student learning outcomes before using the CRA approach were still low with an average value of 57. (2) The application of the CRA approach works well according to the stages. Teacher and student activities have increased in each cycle. (3) student learning outcomes after using the Talking Chips model have increased each cycle. The percentage of classical learning completeness in pre cycle 33% (less), cycle I was 58% (less), in cycle II was 92% (Very High).